A Study to Assess the Effectiveness of Nurse Led Interventions on the Level of Knowledge and Pre-Operative Anxiety among Patients Undergoing Cataract Surgery at Shri Vinoba Bhave Civil Hospital, Silvassa (Global Journal of Medical Research, 2022)
Background: A Cataract is one of the most common disorders affecting the eye and is the leading cause of visual impairment and blindness. Patients who are planning for surgery don#x2019;t have adequate knowledge
Keywords: cataract; nurse led interventions; level of knowledge; pre-operative anxiety